Pengaturan Zonasi dan Pengelolaan Pesisir Laut Teluk Kupang dan Implikasinya Terhadap Pembangunan di Kota Kupang - Muh. Rezha Rasyid; Kotan Y Stefanus; Hernimus Ratu Udju (LPPM Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this research is to analyse the zoning and management of the coastal sea of Kupang Bay and its implications for development in Kupang City. This research is conducted with legal material collection techniques, namely the collection of legal materials from references or literature sources in the form of books, laws, law journals, research-related articles and some from internet sites and other reading sources. The legal materials collected are then analyzed to see the problems related to good faith and processed by drawing conclusions from general problems to concrete problems faced, then presented normatively. The results of this research show: (1) In this study, it has been described at a glance about the various trends of development paradigms, as well as their implications for the development of coastal areas in the era of the establishment of regional autonomy. Although coastal areas generally have strategic potential to become prime movers of regional development, the lack of fulfillment of various strategic prerequisites has led to the insignificant role of coastal and marine-based development sectors in regional development. (2) Zoning arrangements are rules provided to overcome the rigidity of basic rules in the implementation of development. The application of zoning regulation techniques cannot be done immediately, but must be planned from the beginning regarding what techniques will be applied and supported by auditable tools and institutions.